2020
DOI: 10.3389/fpsyg.2020.02223
|View full text |Cite
|
Sign up to set email alerts
|

Iowa Gambling Task and Distortion in Perception of Body Image Among Adolescent Women With Eating Disorders

Abstract: The Iowa gambling task (IGT) is an instrument for the neuropsychological evaluation of cognitive and emotional decision making (DM) processes that was created to test the somatic marker hypothesis (SMH) described by Damasio in 1994. It was initially applied to patients with frontal lobe lesions due to its association with executive functions but was subsequently used on patients with a variety of disorders. Although the DM process is inherently perceptual, few studies have applied the IGT to examine DM process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Asian women tend to show overestimated BWP compared to Western populations where women underestimating BWP is a more critical issue ( Wardle et al, 2006 ). This can be explained as Asian women tend to compare themselves with slim models in the media and idealizing the idea of a thin body ( Martinez-Garcia et al, 2020 ). Moreover, since Asian cultures are more likely to pursue collectivistic societies than Western cultures, Asian women tend to compare their appearance with others, and are more conscious to others’ judgements ( Jung & Lee, 2006 ), leading to the idealization of thinness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian women tend to show overestimated BWP compared to Western populations where women underestimating BWP is a more critical issue ( Wardle et al, 2006 ). This can be explained as Asian women tend to compare themselves with slim models in the media and idealizing the idea of a thin body ( Martinez-Garcia et al, 2020 ). Moreover, since Asian cultures are more likely to pursue collectivistic societies than Western cultures, Asian women tend to compare their appearance with others, and are more conscious to others’ judgements ( Jung & Lee, 2006 ), leading to the idealization of thinness.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that women with overestimated BWP had a higher degree of body shape dissatisfaction and disordered eating attitudes, poorer QoL, and lower self-esteem. Few studies have only focused on females or adolescents, where they have not examined any more than two psychological aspects ( Kim et al, 2018 , Martinez-Garcia et al, 2020 ). A similar study only assessed one psychological symptom, depression, and found that overestimated BWP was positively correlated with depressive symptoms in women ( Abara et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%